Vanadium Oxide Based Electrochromic Energy Storage Devices via Facile Thin Film Preparation - Asuman Tuna; Sermet Koyuncu (Journal of Advanced Research in Natural and Applied Sciences)
The amount of energy utilized in our lives has significantly increased since the invention of electronic devices. Due to this increase in consumption, energy conservation and small-scale energy storage have become important. Smart glass technology is realized by using electrochromic devices prepared from thin films whose transmittance can be controlled under the influence of electric field. Most of theoxidized components of transition metals can be used in electrochromic devices. Vanadium, transition metal, is one of the rare compounds that show coloration in both anodic and cathodic layers. VanadiumOxide thin films show phase change at different temperatures. With this feature, it shows anodic or cathodic differences in oxidation levels. In this study, V2O5 thin films were prepared by annealing at differentthicknesses and temperatures with a spray coating device in order to measure the energy storage capacity of electrochromic devices. Prepared thin film samples were examined by atomic force microscopy (AFM) to determine their surface morphology. Optical and electrochemical properties of thin films were measured with UV-Vis spectrophotometer. Thin films were prepared for use in the anodic layer by coating PEDOT: PSS on the ITO/glass surface. Electrochromic devices were prepared by combining the anodic and cathodic layers with electrolyte gel by sandwich method. Durability and load capacity analyses of the prepared electrochromic devices were carried out.